ТАЛАБАЛАРНИНГ ЎҚУВ-БИЛИШ ФАОЛИЯТИНИ БОШҚАРИШ МОДЕЛЛАРИ - Бектурсынова, Л.Х. (SCIENCE and SOCIETY, 2018)
In the article there have been analyzed the stages and pedagogical-psychologic peculiarities of the models of managing students‘ learning cognitive activity.